Classroom Action Research Mentoring for Teachers to Improve Numeracy Literacy Based on Local Wisdom - Humaidi, Akhmad; Huriaty, Dina; Afriani, Dina (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
The main objectives of this community service activity are (1) to strengthen literacy and numeracy competencies, (2) to make learning more contextual by utilizing local wisdom, and (3) to strengthen numeracy literacy competencies sustainably through Classroom Action Research (CAR). The method used is Participatory Action Research (PAR), which consists of five stages, namely (1) the knowing stage, which is to find a picture of the state of the MGMP Mathematics of Banjar Regency Middle Schools in depth; (2) the understanding stage, which is to understand the main problems of the MGMP Mathematics based on initial observations; (3) the planning stage, which is to compile problem solving based on the results of discussions between partners and the community service team; (4) the action stage, which is to implement a workshop on integrating numeracy literacy with local wisdom through Classroom Action Research; and (5) the changing stage, which is to implement problem solving actions in the form of teacher assistance to practice the material that has been given. The pre-test results showed that the average score was 65.48. However, after the participants completed the activity, the average score on the post-test results increased by 13.5 to 78.97. Practicing teachers who were assisted by the community service team also succeeded in improving learning outcomes. This success is expected to be an inspiration, role model, and discussion partner for other participants. The community service team suggested that similar programs be continued and expanded. Sustainability needs to be encouraged by increasing the independence of participants to practice it in their respective schools.